Organization Of Mathematics Teaching And Modern Mathematics Lesson - Mamatova, Zilolakhon Khabibullokhonovna; Nasaydinova, Nasima (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
In modern education, in the context of systemic reforms aimed at ensuring the quality of teaching in educational institutions, the development of professional skills of future teachers, their modern knowledge, abilities and competencies in innovative technologies, as well as the mastery of advanced foreign experiences, are among the urgent tasks. Modern approaches contribute to increasing the effectiveness of mathematics education, engaging students in the subject, and developing their independent thinking skills. This article discusses modern methods of teaching mathematics, their advantages, and their role in the educational process.